The translation strategies and approaches used by translators of scientific texts from English to Malay - Gurdial Singh, Kulwindr Kaur (Journal of Modern Languages, 2017)
The participants in this study comprised five experienced Malay part-time translators from the University of Malaya who were asked to translate different English language science texts to the Malay language using the think aloud protocol or TAP technique. The transcriptions of their TAPs were analysed and then matched against the direct and indirect language learning strategies proposed by Oxford (1990) and O’Malley and Chamol (1990). It was found that all the main direct and indirect strategies were used by the participants while translating. Besides these, three new strategies were also used. First, they used their own beliefs based on experience on how to translate. Second, they found their own solutions to the problems identified and carried them out. Lastly, they used the discrimination strategy to find an equivalent term in the target language from two or three alternatives identified based on the contextual meaning in the text and the culture of the target readers. From the findings, the researcher proposed her own translation strategies taxonomy. The translation approaches used by the participants were found to be generally the same as those proposed in the translation models by Bell (1991), Sager (1994), and Darwish (1989, 1999).